The Autophagosomal SNARE Protein Syntaxin 17 Is an Essential Factor for the Hepatitis C Virus Life Cycle - Ren, Huimei (J Virol, 2016)
Syntaxin 17 is an autophagosomal SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) protein required for the fusion of autophagosomes with lysosomes to form autolysosomes and thereby to deliver the enclosed contents for degradation. Hepatitis C virus (HCV) induces autophagy. In light of the observation that the number of viral particles formed by HCV-infected cells is much greater than the number of infectious viral particles finally released by HCV-infected cells, the regulation of fusion between autophagosomes and lysosomes might fulfill a key function controlling the number of released virions. HCV-replicating cells possess a decreased amount of syntaxin 17 due to impaired expression and increased turnover of syntaxin 17. Overexpression of syntaxin 17 in HCV-replicating cells diminishes the number of released infectious viral particles and decreases the amount of intracellular retained viral particles by favoring the formation of autolysosomes, in which HCV particles are degraded. Inhibition of lysosomal acidification by bafilomycin rescues the decreased release of virions from syntaxin 17-overexpressing cells, while induction of autophagy by rapamycin enforces the impairment of release under these conditions. Vice versa, inhibition of syntaxin 17 expression by specific small interfering RNAs results in an elevated amount of intracellular retained viral particles and facilitates the release of HCV virions by impairment of autophagosome-lysosome fusion. HCV genome replication, however, is not affected by modulation of syntaxin 17 expression. These data identify syntaxin 17 to be a novel factor controlling the release of HCV. This is achieved by regulation of autophagosome-lysosome fusion, which affects the equilibrium between the release of infectious viral particles and lysosomal degradation of intracellular retained viral particles. IMPORTANCE Hepatitis C virus (HCV) induces autophagy. Syntaxin 17 is an autophagosomal SNARE protein required for the fusion of autophagosomes with lysosomes. In HCV-infected cells, a major fraction of the de novo-synthesized viral particles is not released but is intracellularly degraded. In this context, the effect of HCV on the amount and distribution of syntaxin 17 and the relevance of syntaxin 17 for the viral life cycle were investigated. This study demonstrates that the amount of syntaxin 17 decreased in HCV-replicating cells. In addition, syntaxin 17 is identified to be a novel factor controlling the release of HCV, and the relevance of autophagosome-lysosome fusion as a regulator of the amount of released viral particles is revealed. Taken together, these findings indicate that syntaxin 17 is involved in the regulation of autophagosome-lysosome fusion and thereby affects the equilibrium between the release of infectious viral particles and the lysosomal degradation of intracellularly retained viral particles.